2021
DOI: 10.1371/journal.pone.0245766
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions to promote pesticide safety and reduce pesticide exposure in agricultural health studies: A systematic review

Abstract: Objective There is a relationship between pesticide exposure and farmworkers’ health. Well-conducted evaluations can provide an insight into how to develop and implement more effective interventions to prevent farmers and farmworkers’ exposure to pesticides. This review aimed to summarize the literature on the effectiveness of interventions to promote pesticide safety and reduce pesticide exposure among farmers and farmworkers. Methods A comprehensive search on PubMed, Embase, ISI Web of Science, Scopus, Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 47 publications
1
18
1
Order By: Relevance
“…In practice, farmers even have different perceptions about the benefits and hazards of pesticides and consequently they choose or select pesticides based on different variables and criteria [35][36][37]. Therefore, understanding the behavioral drivers of farmers' pesticide use is indispensable to promote and design the campaign of pesticide safe behavior [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…In practice, farmers even have different perceptions about the benefits and hazards of pesticides and consequently they choose or select pesticides based on different variables and criteria [35][36][37]. Therefore, understanding the behavioral drivers of farmers' pesticide use is indispensable to promote and design the campaign of pesticide safe behavior [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Salzsar and Rand [15] found that more risk-averse farmers use less pesticide. Farmers' perceptions of the risks in human health posed by pesticides, which can decrease their pesticide expenditure, and their risk attitude is the main factor of farmers' pesticide application behavior (see for instance [16][17][18][19][20][21]). Gong et al [22] have found that risk aversion significantly increases pesticide use.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, farmworkers frequently lack adequate knowledge about the occupational hazards they face and the relevant risk factors [9]. In this context, previous studies have indicated that safety training and educational interventions might increase protective behaviors [7,[10][11][12][13]. Nevertheless, the evidence of easy and effective interventional measures for pesticide protection is limited, especially for rural Asia [10].…”
Section: Introductionmentioning
confidence: 99%